2013
DOI: 10.1179/2049396713y.0000000046
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and plausibility of the Pliocene lignite hypothesis in explaining the etiology of Balkan endemic nephropathy

Abstract: Background: Balkan endemic nephropathy (BEN) is a chronic, tubulointerstitial renal disease often accompanied by urothelial cancer that has a lethality of nearly 100%. Introduction: One of the many factors that have been proposed to play an etiological role in BEN is exposure to organic compounds from Pliocene lignite coal deposits via the drinking water in endemic areas. Objectives: The objective of this study was to systematically evaluate the role of the tenets of the Pliocene lignite hypothesis in the etio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 83 publications
2
5
0
2
Order By: Relevance
“…In almost all the water samples, phthalates, the most widespread man-made contaminants, were found. This finding is in line with the earlier studies where they found abundant and numerous phthalates (Bunnell et al, 2006;Maharaj, 2014). Bunnell et al (2006) suggested that these phthalates are mainly originated from PVC well casings and plastic parts of the pump systems.…”
Section: Organic Analysessupporting
confidence: 91%
See 3 more Smart Citations
“…In almost all the water samples, phthalates, the most widespread man-made contaminants, were found. This finding is in line with the earlier studies where they found abundant and numerous phthalates (Bunnell et al, 2006;Maharaj, 2014). Bunnell et al (2006) suggested that these phthalates are mainly originated from PVC well casings and plastic parts of the pump systems.…”
Section: Organic Analysessupporting
confidence: 91%
“…Earlier studies indicated that, in well water samples taken from BEN endemic areas, the concentration and the number of organic compounds are higher than those of the non-endemic regions (Feder et al, 1991;Maharaj, 2014;Orem et al, 2002;2007). On the other hand, the GC-MS results of the present study revealed that the organic compound composition of all the water samples is similar to each other.…”
Section: Organic Analysessupporting
confidence: 64%
See 2 more Smart Citations
“…In contrast, a study by Voice et al ( 2006 ) found no detectable levels of any of the 16 priority pollutants designated by the US Environmental Protection Agency were found in water samples throughout the Balkans, and no difference in waterborne concentrations of these pollutants between BEN and non-endemic villages (Voice et al 2006 ). These findings suggest that the Pliocene lignite hypothesis is limited to the spatial association originally proposed in BEN (Maharaj 2014 ). Therefore, exposures of individuals living in endemic areas to the compounds from the lignite deposits are not relevant for the aetiology of BEN.…”
Section: Exogenous Factors Relevant For Ben Aetiologymentioning
confidence: 72%